2005
DOI: 10.1001/jama.294.23.3003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Air Pollution Exposure and Acceleration of Atherosclerosis and Vascular Inflammation in an Animal Model

Abstract: In an apoE-/- mouse model, long-term exposure to low concentration of PM2.5 altered vasomotor tone, induced vascular inflammation, and potentiated atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
513
1
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 754 publications
(552 citation statements)
references
References 35 publications
26
513
1
12
Order By: Relevance
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31).…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 99%
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31).…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 99%
“…A sudden surge in the level of PM has been linked to increased morbidity and mortality due to cardiorespiratory events, including asthma, chronic obstructive pulmonary disease (COPD), and atherosclerosis [1][2][3][4][5][6][7][8][9][10][11][12]. Both in vitro and in vivo studies of the health effects of ambient PM have identified the generation of oxidative stress as one of the major mechanisms by which air pollution particles exert adverse biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential mechanism have been postulated to cause the increase in atherotrombotic events, such as activation of inflammatory pathways, production of reactive oxygen species and alterations in vascular tone (Pope CA et al, 2004). There is another study showing that fine particulate exposure accelerates the development of atherosclerosis in animal model (Sun Q et al, 2005).…”
Section: Air Pollution and Cardiovascular Diseases (Cvd)mentioning
confidence: 99%